STRUCTURAL PROPERTIES AND CRYSTALLIZATION OF DENSIFIED BORON SILICON NITRIDE: INSIGHTS FROM MOLECULAR DYNAMICS SIMULATION - Cong Thanh, Dinh; Van Vinh, Le (HNUE Journal of Science: Journal of Natural Sciences, 2026)
We used molecular dynamics (MD) simulations to investigate the structural properties of boron silicon nitride (B-Si-N) under high pressure. The B-Si-N sample was cooled from 5000 K to 300 K at a constant pressure of 60 GPa. At 4000 K and 3500 K, the structure remained disordered. As the sample was cooled, a phase transition occurred between 3500 K and 3000 K. Common-neighbor analysis (CNA) showed that nitrogen atoms in the Si-N-rich region began to form crystalline clusters with face-centered cubic (FCC) and hexagonal close-packed (HCP) arrangements. Most clusters adopted FCC-like local ordering of nitrogen atoms, whereas a smaller fraction exhibited HCP ordering. The crystallization mechanism is discussed in detail.